UPAYA PEMBERDAYAAN KOPERASI DI INDONESIA - Hesti Respatiningsih (SEGMEN Jurnal Manajemen dan Bisnis, 2006)
Cooperative empowering in Indonesia is necessary to be done through the effort which has the capability to build cooperative as a basic power of society and can be reliable. In effort of cooperative empowering can be done: implementing the good corporate governance (GCG) principles, performing cooperative professionally, reconstructing the management of cooperative and creating goodwill and birocracy politicalwill. Keywords: cooperative empowering, good corporate government, goodwill, and politicalwill